Metode Penelitian Hadist Musykil - Lukmanul Hakim (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2011)
Abstruse hadith is caused by several things, such as the content difficult to know or to prove by the conventional sense, the contradiction with the other hadith, even with the Koran. Although this kind of hadith is abstruse, in terms of quality of it is very strong, so it should be adopted as a hadith. Hadith scholars, to some extent, address the investigation, either through the understanding of the text, as well as tighten sanad validity. This article, is trying to investigate how the techniques introduced scholars of hadith, in particular, the abstruse, as well as methods of understanding it.